Social Work in Kosovo, Development, Challenges and Achievements in Mitigating Negative Social Phenomena - Shaqiri, Adile; Koci, Magbule (European Journal of Social Science Education and Research, 2023)
The purpose of this paper is to analyze the importance and impact of Social Work in mitigating negative social phenomena in Kosovo. Kosovo is a country in transition, a country with a high level of education, low economic development, high unemployment rate, high poverty rate, political instability, where we conclude that the increase of negative social phenomena such as: violence in the family, trafficking in human beings, abused children, dysfunctional families, divorce, abuse with psychoactive substances by young people, determine the inevitable need for social work in Kosovo. The thesis of this study is: What is the impact of Social Work in Kosovo in preventing negative phenomena such as domestic violence, violence against women and children? The main focus of this study is the analysis on the necessity and need for strengthening Social Work in Kosovo, the efforts, challenges, confrontations and clashes between time periods and political changes and systems that have already led to a new understanding of Social Work in Kosovo. Within the paper, the main areas taken for study are related to the principles of social work, aspects of social work, the need for social work, professional opportunities in the field of social work and the role of the Social Worker, which are the main axis of this paper. The summary with conclusions and recommendations will be at the end of this.